KLASIFIKASI SISWA BERDASARKAN MATA PELAJARAN LINTAS MINAT MENGGUNAKAN METODE DECISION TREE C4.5 - Suherman; Purnamasari, Marlia; Fitriani Dwi Hastuti (Jurnal Sistem Informasi, 2021)
The 2013 curriculum is designed to give students the opportunity to learn based on students ' interests. In addition to selecting subjects in a particular interest, students are also given the opportunity to take cross-interest subjects. SMA Negeri 1 Anyer is one of the schools that have implemented cross-interest programs. In the process of determining the cross-interest class, the school is still experiencing constraints i.e. not the specificity of students who have an interest in certain subjects, and in the process of electoral elections determined by the school. This research aims to classify students based on students ' interests and talents in specific subjects. The method used is the Decision Tree and C4.5 algorithm. This study gained an accuracy value of 82.82%. Research generates a cross-country class determination system. This classification Model can assist students in determining cross-interest and can be used as a reference alternative for BK teachers to be able to group students based on students ' interests and talents.